Climate Warming Since the Holocene Accelerates West–East Communication for the Eurasian Temperate Water Strider Species Aquarius paludum. (28th April 2022) - Ye, Zhen; Yuan, Juanjuan; Damgaard, Jakob; Berchi, Gavril Marius; Cianferoni, Fabio; Pintar, Matthew R.; Olosutean, Horea; Zhu, Xiuxiu; Jiang, Kun; Yang, Xin; Fu, Siying; Bu, Wenjun
Abstract: Holocene climate warming has dramatically altered biological diversity and distributions. Recent human-induced emissions of greenhouse gases will exacerbate global warming and thus induce threats to cold-adapted taxa. However, the impacts of this major climate change on transcontinental temperate species are still poorly understood. Here, we generated extensive genomic datasets for a water strider, Aquarius paludum, which was sampled across its entire distribution in Eurasia and used these datasets in combination with ecological niche modeling (ENM) to elucidate the influence of the Holocene and future climate warming on its population structure and demographic history. We found that A . paludum consisted of two phylogeographic lineages that diverged in the middle Pleistocene, which resulted in a "west–east component" genetic pattern that was probably triggered by Central Asia-Mongoxin aridification and Pleistocene glaciations. The diverged western and eastern lineages had a second contact in the Holocene, which shaped a temporary hybrid zone located at the boundary of the arid–semiarid regions of China. Future predictions detected a potentially novel northern corridor to connect the western and eastern populations, indicating west–east gene flow would possibly continue to intensify under future warming climate conditions. Further integrating phylogeographic and ENM analyses of multiple Eurasian temperate taxa based on published studies reinforced our findings on the "west–east component" genetic pattern and the predicted future northern corridor for A . paludum . Our study provided a detailed paradigm from a phylogeographic perspective of how transcontinental temperate species differ from cold-adapted taxa in their response to climate warming.